The 2020 Pocari Sweat TV Advertisement’s Interpretation - Dewi Nuryanti; Annisa A. T. Basuki (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2020)
This research is aimed to analyze the interpretation of the Pocari Sweat advertisement 2020. The aims are to identify the interpretation meaning of the sentence in the advertisement itself, to identify the way that makes Pocari Sweat become an effective Advertisement that uses the narrative form, and to identify the effects of advertisement that uses the narrative explanation. The writer uses the theory of Dodd 2012 and Rossalotos 2015 to do the research. This research uses the qualitative method. The result of this research shows confidence, freedom, and spirit. Besides that, the way that makes this advertisement effective is the message, before it is too late and regrets getting old. In the conflict, there is a struggle with character confidence. The character, in this advertisement, is a character who builds and gives the message. The plot, this advertisement gives a sequence from the introduction, the conflict, and the result of the conflict itself. The last, the effects of this research provide a positive effect on teenagers. The research also found the moral values in this advertisement: Persistence, keep strong, and never give up.